Equations l,V and Vl all have the same solution set.

We can obtain V from l by multiplying both sides of l by 3 then applying symmetric property(switching sides):

\((x-5)(3)=(3x+7)(3)\)

\(3x-15=9x+21\)

\(9x+21=3x-15\)

We can obtain Vl from l by multiplying both sides of l by 100 then applying commutative property on the left side:

\(\frac{x-5}{100}=\frac{3x+7}{100}\)

\(\frac{x}{100-0.05}=\frac{3x}{100+0.07}\)

\(\frac{-0.05+x}{100}=\frac{3x}{100}+0.07\)

Equations ll and lV have the same solution set.

We can obtain lV from ll by multiplying both sides of ll by 2 then substracting 4 from both sides:

\((3x-6)(2)=(7x+8)(2)\)

\(6x-12=14x+16\)

\(6x-12-4=14x+16-4\)

\(6x-16=14x+12\)

Equations lll does not have the same solution set as the other equations since it cannot be transformed from l or ll.

Results:l,V, and Vl all have the same solution set.

ll and lV have the same solution set.

lll does not have the same solution set as the other equations.